Korean culture in the global age
1 online resource.
Keywords: "Since the late 1990s, South Korean cultural products such as pop music, TV drama, and film have shaped the country's image around the world. This book explores these three internationally best-known media of the Korean Wave global phenomenon, along with a less commonly featured aspect, K-literature. Iconic images of South Korea today include stylish music groups like BTS and Blackpink, appealing dramas, and a range of films and digital comics (manhwa). Alongside associations with glitz and glamor are darker impressions: continuing political division, malaise over a war that never really ended. Korean Culture in the Global Age focuses on these and other facets of South Korea's constantly changing international image to show how it has come to command worldwide attention. In recent years, readers in a growing number of languages have discovered the talent of South Korean authors through the effort of countless translators. Showing developments in and occasional connections between themes in K-pop, K-drama, K-film, and K-literature, the book provides a more comprehensive view of contemporary South Korean culture. This volume will interest researchers and students of Korean Studies, Asian Studies, Asian-American Studies, popular music, film studies, migration and diaspora studies, and world literature"-- Provided by publisher.